The necessity of continuing cervical cancer screening of elderly Korean women aged 65 years or older. Issue 10 (30th July 2022) - Cho, Sumin; Lee, Seon‐Mi; Lee, Sanghoon; Cho, Hyun‐Woong; Min, Kyung‐Jin; Hong, Jin‐Hwa; Song, Jae‐Yun; Lee, Jae‐Kwan; Lee, Nak‐Woo
Abstract: Background: Although the incidence of cervical cancer has decreased since the 1980s in Korea, it remains high among the elderly women. This study evaluated the suitability of cervical cancer screening for elderly Korean women aged ≥65 years according to recommendations by the American Society of Cytopathology and American Society for Colposcopy and Cervical Pathology. Methods: We retrospectively reviewed the records of patients who underwent cervical cancer screening, followed by liquid‐based Pap test, human papillomavirus (HPV) test, and colposcopic punch biopsy at two academic hospitals from May 2008 to May 2018. The participants were divided into two groups <65 and ≥65 years old. Logistic regression analysis was performed to evaluate the association between cytology tests, HPV tests and the occurrence of high‐risk lesions, ≥cervical intraepithelial neoplasia2 (CIN2). Results: The mean patient age was 49.02 ± 15.437 (range 15–91) years. No patients aged <25 years showed atypical squamous cell‐cannot exclude high grade (ASC‐H), squamous cell carcinoma (SCC), or adenocarcinoma (ADC). The incidence of high‐grade squamous intraepithelial lesion (HISL) (39.7%) and ≥CIN 3 (40.2%) was significantly higher in patients ≥65 years of age than in other age groups. However, patients ≥65 years showed increased HSIL and HPV negativity and ASC‐H, HSIL, and HPV positivity in those with ≥CIN 2 (both p  = .043). Conclusion: Korean women aged ≥65 years should undergo cervical cancer screening. The relevance of HPV or Cytology test alone or co‐test for screening should be evaluated in this population.